(3GdJYQja hGdCYdGe ajeG oCHge aj GdbQBf ef GdCSeGA hGdCYdGes - (3GdSgjdj , YHO GdQMef Hf YHO Gddg Hf CMeO Hf GUHZ GdNKYej CHh GdbGSe, CHh GdbGSe,J (B581 (3g` s ((3eMeO Hf YeQ GdHRGQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde BOe GdCSeGA hTQa HYde Ojfg GdYdeGA GdN s
(3BNQgG (B:s
(3hef Gddg YR hLd CSCd GdCLQ hEjGg GSJhgH LRjd GdaNQ heMWI GdhRQ Efg NjQ GdefYejf hCQMef GdQGMejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B147s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B413 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B41 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs